Islamic Instructional Methodology in the Thought of ‘Ali Aḥmad Madzkūr: A Theoretical Study - Maulana, Asep; Safrullah, Dendi Yuda (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study responds to the increasing need to renew Islamic instructional methodologies in light of contemporary pedagogical developments and 21st-century competency demands. The contributions of ʿAlī Aḥmad Madzkūr are central to this effort, as he proposes an educational framework that integrates revelation, rational inquiry, and lived experience as the epistemic foundation of Islamic pedagogy. The research examines four principal methods formulated by Madzkūr—exemplary modeling, dialogic learning, problem-solving, and observation combined with experimentation—while situating them in conversation with Western educational perspectives, especially those of Dewey, Kolb, and Bandura. It also analyzes his emphasis on instructional media as tools for clarifying abstract ideas, fostering active engagement, and linking theoretical concepts with practical realities, supported by a reflective-diagnostic evaluation system. Using a library-based research design, the study employs thematic, comparative, and synthetic analyses grounded in Madzkūr’s primary works and current pedagogical discourse. The findings show that his approach is integrative, merging ethical formation, rational development, and empirical inquiry into a unified pedagogical structure. Modeling cultivates moral character, discussion strengthens analytical thinking, observation and experimentation develop scientific habits of mind, and problem-solving enhances higher-order reasoning. Altogether, Madzkūr’s framework aligns with modern educational theories while offering a distinctive spiritual dimension, making it a promising and adaptable model for Islamic education.